A novel swine model of the acute respiratory distress syndrome using clinically relevant injury exposures. Issue 9 (15th May 2021) - Tiba, Mohamad H.; McCracken, Brendan M.; Leander, Danielle C.; Colmenero, Carmen I.; Nemzek, Jean A.; Sjoding, Michael W.; Konopka, Kristine E.; Flott, Thomas L.; VanEpps, J. Scott; Daniels, Rodney C.; Ward, Kevin R.; Stringer, Kathleen A.; et al.
Abstract: To date, existing animal models of the acute respiratory distress syndrome (ARDS) have failed to translate preclinical discoveries into effective pharmacotherapy or diagnostic biomarkers. To address this translational gap, we developed a high‐fidelity swine model of ARDS utilizing clinically relevant lung injury exposures. Fourteen male swine were anesthetized, mechanically ventilated, and surgically instrumented for hemodynamic monitoring, blood, and tissue sampling. Animals were allocated to one of three groups: (1) Indirect lung injury only : animals were inoculated by direct injection of Escherichia coli into the kidney parenchyma, provoking systemic inflammation and distributive shock physiology; (2) Direct lung injury only : animals received volutrauma, hyperoxia, and bronchoscope‐delivered gastric particles; (3) Combined indirect and direct lung injury : animals were administered both above‐described indirect and direct lung injury exposures. Animals were monitored for up to 12 h, with serial collection of physiologic data, blood samples, and radiographic imaging. Lung tissue was acquired postmortem for pathological examination. In contrast to indirect lung injury only and direct lung injury only groups, animals in the combined indirect and direct lung injury group exhibited all of the physiological, radiographic, and histopathologic hallmarks of human ARDS: impaired gas exchange (mean PaO2 /FiO2 ratio 124.8 ± 63.8), diffuse bilateral opacities on chest radiographs, and extensive pathologic evidence of diffuse alveolar damage. Our novel porcine model of ARDS, built on clinically relevant lung injury exposures, faithfully recapitulates the physiologic, radiographic, and histopathologic features of human ARDS and fills a crucial gap in the translational study of human lung injury. Abstract : Our novel porcine model of the acute respiratory distress syndrome, built on clinically‐relevant lung injury exposures, faithfully recapitulates the physiologic, radiographic, and histopathologic features of human ARDS, and fills a crucial gap in the translational study of human lung injury.